KUALITAS PELAYANAN PADA KANTOR PELAYANAN PAJAK PRATAMA BANGKINANG - Azmi, Novri Dwi; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Tax Office Primary Bangkinang is a government institution that has a fundamental duty and taxation affairs organized as tax dues can be used for the development and prosperity of the nation of Indonesia. Taxes collected by the Government used to maintain the viability of the state and sources of financing expenditures incurred by the government to run the government. The tax itself is a mandatory contribution to the state owed by the individual or entity coercive. Of understanding shows that society shall contribute to the country, and the public should get a quality service. But the fact remains a bottleneck services, such as the Society is still waiting for a long time in the process of printing proofs tax reporting, due to the network system in the office is often problematic. The purpose of this study was to determine how the quality of service at the Tax Office Primary Bangkinang.The concept of the theory that researchers use is according toZeithhaml-Berry-Parasuraman there are several dimensions of service quality are: Realibility, Responsiveness, Assurance, Empathy and Tangibles. This research is a qualitative descriptive study, which used data collection techniques by observation, interviews and data collection with documents obtained from informants research that has been determined based on snowball sampling technique.From the results of this study indicate that the quality of service at the Tax Office Primary Bangkinang not running optimally. Factors that influence is a means of tax services, the quality of the knowledge and experience of employees and employee ethics.Keywords: Quality, Service, STO Bangkinang